Working from home remains a select privilege: it’s time to fix our national employment standards - Dayaram, Kantha; Fitzgerald, Scott; McKenna, Stephen (2020)
The number of Australians working from home has soared during the COVID-19 crisis. Latest data from the Australian Bureau of Statistics shows 46% of the workforce worked from home in late April and early May. By comparison, the bureau’s 2019 data showed slightly less than a third saying they “regularly worked from home” – a number likely inflated by those catching up on work from the office. For many this has been the first real taste not just of full time teleworking, but any flexible working arrangements – something that under minimum employment laws remain a privilege for a select few.